Evaluation of the Tramline Sign in the Prediction of Placenta Accreta Spectrum and Perioperative Outcomes in Anterior Placenta Previa - Dall’Asta, Andrea; Forlani, Francesco; Shah, Harsha; Paramasivam, Gowrishankar; Yazbek, Joseph; Bourne, Tom; Calì, Giuseppe; Lees, Christoph (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Purpose To evaluate perioperative outcomes and the prognostic role of the tramline sign in a cohort of women with anterior placenta previa.Materials and Methods Retrospective analysis of 3D ultrasound volumes from women with anterior placenta previa who underwent ultrasound examination beyond 32 weeks. 3D and 3D color volumes were obtained from a sagittal section of the uterus bisecting a partially full bladder and processed using Crystal Vue and Crystal Vue Flow rendering to look for the “tramline sign”. “Partial obliteration” was defined as a loss of some or part of the uterine-serosal interface and “full obliteration” as when both interfaces were interrupted. Postnatal ascertainment of placenta accreta spectrum (PAS) was confirmed by findings recorded intraoperatively or on a pathology report.Results 65 cases were included. The tramline sign was “partially” (17) or “fully” (19) obliterated in 36 cases (55.4 %), and present in 29 (44.6 %). Obliteration was associated with earlier gestational age at delivery (35 + 1 (26 + 3–38 + 3) vs. 36 + 4 (25 + 3–38 + 0) weeks, p = 0.005), greater estimated blood loss (800 (400–11 000) vs. 600 (300–2100) mls, p = 0.003), longer operative time (155 (60–240) vs. 54 (25–80) minutes, p < 0.001), higher rate of hysterectomy (97.2 % vs. 0.0 %, p < 0.001), longer postoperative admission (7 (3–19) vs. 3 (1–5) days, p < 0.001) and a 100 % rate of postnatal diagnosis of PAS. The finding of an “obliterated” tramline sign identified all women that required hysterectomy and all cases of PAS.Conclusion A “partially or fully obliterated” tramline sign is strongly associated with indicators of operative complexity, the postnatal confirmation of PAS, and the need for peripartum hysterectomy.
Keywords: abnormally invasive placenta; morbidly adherent placenta; 3D ultrasound; Crystal Vue; cesarean hysterectomy